2014
DOI: 10.3384/diss.diva-65356
|View full text |Cite
|
Sign up to set email alerts
|

Talet om tekniska system: förväntningar, traditioner och skolverkligheter

Abstract: PrologFöreläsaren hade kommit till slutet av 1700-talet och ångmaskinens intåg. Det hela rörde teknikhistorisk utveckling och jag var intresserad eftersom jag själv hade undervisat om de viktiga steg teknikutvecklingen tagit, de nya uppfinningar som sett världens ljus och i kraft av sin genialitet och sitt genomslag ofta påverkat både oss människor och vår omvärld på ett genomgripande sätt. Där jag förväntade mig en inträngande redogörelse för övergången från intern till extern kondensering av ångan, från enke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
8

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
1
10
0
8
Order By: Relevance
“…This study consequently confirms the results of Klasander (2010) who concluded that system understanding among teachers is hampered by an exaggerated focus on artefacts and components. Svensson claimed that understanding the artefacts in a system can be a good starting point for understanding the whole system (Svensson 2011), and we can see some such understanding in that the students could name some components and relate them to each other.…”
Section: Concluding Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study consequently confirms the results of Klasander (2010) who concluded that system understanding among teachers is hampered by an exaggerated focus on artefacts and components. Svensson claimed that understanding the artefacts in a system can be a good starting point for understanding the whole system (Svensson 2011), and we can see some such understanding in that the students could name some components and relate them to each other.…”
Section: Concluding Discussionsupporting
confidence: 80%
“…Klasander concluded that systems thinking among teachers is often hampered either by a focus on scientific, reductionist aspects of systems or a focus on single artefacts (Klasander 2010). Svensson and Klasander studied how two groups of technology teachers plan their teaching about technological systems in lower secondary school.…”
Section: Pupils' and Teachers' Conceptions Of Technological Systemsmentioning
confidence: 99%
“…The reason for this could be that content is assessed in other ways. It could also indicate that it is commonly omitted when teaching the subject in the participating schools, as was the case in many schools according to Swedish School Inspectorate (Skolinspektionen 2014;Klasander 2010). …”
Section: Resultsmentioning
confidence: 99%
“…This separation of Science and Technology within the curriculum was maintained in the last curriculum reform, in 2011. However, in practice in the classroom, "a hegemony of science" has dominated teaching, treating technology as applied science or mainly scientific aspects of technology (Klasander 2010). This persistent form of a boundary that encapsulates Technology within Science is also present in important educational policy texts in Sweden.…”
Section: The Relationship Between Technology and Sciencementioning
confidence: 99%
“…4 At the same time, we can conclude that, for example, the systems perspective is largely missing. Ever since the 1970s, historians and sociologists of technology have studied technology as systems, since technology not only consists of separate objects but also large technological systems with other structures, functions and dynamics than the single objects by themselves (Hughes 1987;Klasander 2010). The so-called Actor Network Theory also illuminates the fact that technology can have the ability to "act" together with human actors in actor-networks, in which these "actants" constitute driving forces in the development of technology together with humans (Latour 1987;Hård and Jamison 2005).…”
Section: Studying School Technology As An Historical Phenomenonmentioning
confidence: 99%